Problema de alocação de viaturas policiais: estudo de caso na cidade de João Pessoa-PB - Silva, Valtania Ferreira da (2014)
Find emergency public services falls into one of the classic optimization problems where points are available for candidates who are chosen, among them, those that optimize the efficiency criteria established, to find a limited number of facilities. The set of candidate sites have great influence on the final solution generated by a model location . In the research, three strategies were used to elect local candidates to position the cars of police : decision of the Security Manager , p-median model and method of clustering k-means. With the support of Geographical Information Systems (GIS ) it was possible to georeference the occurrences of crimes , to visualize the distribution of selected local candidates and identify the presence of hotspots of crime. Aiming to solve the problem of allocating vehicles adopted two approaches : exact and heuristic . Therefore, two hybrid meta - heuristics were implemented - GRASP combined with VND and GRASP with exact model. They obtained same or very approximate solutions of the optimal solution . It was developed a system of spatial decision support based on the solution of the formulation of the problem of locating facilities with restricted coverage and backup coverage. It is a Web tool built with by WebGIS technology